Credit card program value maximization with promotion density for product discounts in shopping malls - CHANG, Rae M. (Institutional Knowledge at Singapore Management University, 2012)
We model value maximization of credit card programs for shopping malls, when card customerscan obtain product discounts of different percentages in the presence of promotion density andcompetition. Our results suggest strategies for quantitatively evaluating the trade-offs in valueoutcomes when consumer sensitivity to product discounting varies.